Hermeneutika Hadis Zakariya Ouzon - Mahfudh, Hasan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2014)
This paper examines the theory hermeneutics want Zakaria Ouzon tradition. Hermeneutic theory is formulated from Ouzon ideas contained in the book Jinâyat al-Bukhârî. After describing and analyzing associated with Ouzon criticism against al-Bukhârî, it can be concluded that the hermeneutics Ouzon is subjective hermeneutics flow model with critical hermeneutics. Hermeneutics Ouzon provide significant implications in the process of autonomization text, where he had been let go by the hadith text is no longer leaning on the Apostle automatically cutting off transmission structure tradition. Research on sanad no longer be important as well as the study of hadith text historicity. The implications of hermeneutics Ouzon on the next stage is to shift the hermeneutic epistemology of classical tradition or understanding of the orientation of hadith criticism can only be done by examining each of the structures of tradition in contemporary hermeneutics Ouzon style. In the structure Ouzon hermeneutic tradition, a tradition critic confronted directly with the texts listed in the Kutub al-Sittah